Contribuições do software GeoGebra no ensino de funções algébricas em tempos de ensino remoto - SILVA, Bárbara Gaia Barreto da (2022)
March 2020, Brazilian schools and universities suspended face-to-face classes due to the COVID-19 pandemic, students and teachers to an abrupt change in the teaching and learning process amid the need for social isolation. With the authorization of Emergency Remote Teaching (ERE) there was a need to include digital technologies in education. The present work aims to contest the contributions of the course on algebraic functions through the medium, from the analysis of the virtual teaching course applied to students. The study method used was the graphic research with the development of two pedagogical workshops via Google Meet in which a class/review of the contents of functions and application of activities of visualizations of constructed through the tools of the Geogebra software was presented. The proposed results in teaching the use of proposed mathematics.